The psychology of video on demand (VoD) consumption and binge-watching typologies: how platforms may be designed to optimise user autonomy - Parkes, Joanne (2025)
‘Binge-watching’ has been in the vernacular for 20 plus years and, according to Forbes [1], has been included in the Oxford English Dictionary since 2018. Here, it is defined as "watching multiple episodes of a television show consecutively or in rapid succession". The facility for a consumer to watch what they want, when they want to, has allowed them to avoid interruption and fully immerse themselves in a narrative, but it’s not without its downsides, which are worthy of consideration, not least for the sheer volume of consumers worldwide. For example, Netflix, the largest paid-for Video on Demand (VoD) broadcaster globally (according to a number of sources [2][3][4][5]), has a consumer base of more than 230 million [6] who at the height of the pandemic in 2020, were watching an average of 3.2 hours per day [2]. For some, there exists a gap between TV (terrestrial broadcast & VoD) consumption intentions and behaviour which may be explained by several psychological drivers such as social pressure; VoD interface design; content narrative and neutralisation effect. This research adopted a mixed methods approach combining qualitative and quantitative data to investigate this gap, following an exploratory sequential design of semi-structured depth interviews, surveys, analysis of viewing data and industry dialogue. The research addressed how platforms might be designed to optimise user autonomy in VoD consumption, examining what constitutes binge-watching, its associated positive and negative aspects, how digital media interfaces influence viewer autonomy, and what features might better serve consumers. This paper aims to address the following research question: How might platforms be designed to optimise user autonomy in VoD consumption? To do this, the researcher has sought to first address the following: • Research Question 1. What constitutes binge-watching, how might it be defined? • Research Question 2. What positive and or negative aspects may be associated with binge-watching? • Research Question 3. What aspects of Digital Media interfaces (if any) reduce consumer autonomy in their viewing behaviours? • Research Question 4. What inter-personalisation features of the interface might better serve the consumer? In order to address these questions, the research approach adopted four interconnected studies: 1. A qualitative exploration of consumer experiences through in-depth interviews, providing rich, contextual data on binge-watching behaviours and perceptions. 2. A quantitative survey on viewing habits and attitudes that allowed for statistical analysis and generalisation of findings to a broader population. 3. An unobtrusive measures study involving the analysis of BBC iPlayer viewing data and related Twitter discourse, that offered insights into real-world viewing patterns and social media engagement around binge-watching. 4. Industry dialogues with key decision-makers and designers, bridging the gap between academic research and practical application in VoD interface design. This comprehensive approach provided a holistic understanding of binge-watching, connecting empirical findings with real-world applications. A key contribution is the development of a novel framework for understanding binge-watching through viewing typologies mapped along dimensions of duration, frequency, and compulsion. This framework intentionally avoids defining specific thresholds, allowing for flexible application across different research contexts and methodologies. The research identified five distinct viewing typologies: Routine Episodic Streaming, Compulsive Streaming, Non-Consequential Recreational Streaming, Periodic Streaming Strategist, and Passive Streaming. Key findings revealed that binge-watching cannot be understood through simple time-based measures. The research demonstrated that while auto-play features significantly influence viewing behaviour (reported by 85% of survey respondents), viewers express strong interest in features supporting more intentional viewing patterns. Analysis of actual viewing data from BBC iPlayer showed how release strategies can impact viewing patterns, with some viewers consuming up to ten episodes (approximately 7.9 hours) on the first day of release. The framework shows promise beyond media consumption, offering potential applications for understanding engagement patterns across various domains of human behaviour. The research has significant implications for both academia and industry, contributing to theoretical understanding while providing practical guidance for developing more user-centric streaming interfaces. By integrating perspectives from viewers, data analysis, and industry professionals, this research aims to influence industry practices in ways that better serve viewer needs and wellbeing, while contributing to ongoing dialogue about corporate responsibility in the digital age.